5-fluorouracil chemotherapy-induced cardiotoxicity: studies from clinic to culture - Hammond, Stephen Thomas (Kansas State University, 2023)
5-fluorouracil (5FU) chemotherapy has remained a key component of numerous cancer treatment regimens since its inception in 1957. Despite high treatment efficacy and association with improved survival outcomes, 5-FU treatment can elicit a varying degree of symptomatic and/or asymptomatic cardiotoxicity, occurring in up to 30% of treated patients. Onset of these maladies often prompts deviation from preferred treatment regimens and can negatively influence patient survival outcomes. To date, the mechanisms responsible for 5-FU cardiotoxicity remain poorly understood, with the most prominent theory suggesting a direct effect of the drug on the vascular endothelium/and or smooth muscle. Therefore, the primary aim of the present dissertation was to take a ‘clinic to culture’ approach to better understanding how 5-FU chemotherapy impacts the cardiovascular system with special emphasis on the vasculature. In chapter 2, we demonstrate reductions in cutaneous microvascular reactivity—presumably via endothelium dependent mechanisms—in patients undergoing treatment for cancer with 5-FU based regimens. Given alterations in endothelial function are a precursor to long-term vascular sequela such as vascular calcification, this led us to hypothesize that 5-FU exposure may predispose aortic smooth muscle cells to the development of calcium deposition in chapter 3. To test this hypothesis, we collected aortic smooth muscle cells from rats treated with a clinically relevant dose of 5-FU or volume matched saline. We found that cells derived from 5-FU treated animals developed a greater degree of calcium deposition when stimulated with a calcification inducing media than cells treated with normal growth media. Interestingly, this finding was not reciprocated in cells derived from saline treated animals. Follow-up experiments in which cells from saline treated animals were cultured with an in vitro dose of 5-FU had higher concentrations of calcium than untreated cells. Findings from this study highlight the need for more data on the potential long-term vascular consequences of 5-FU chemotherapy. In chapter 4, we sought to test the efficacy of acute exercise as a modality to prevent 5-FU cardiotoxicity. We hypothesized that acute exercise prior to treatment with a clinically based 5-FU infusion would prevent the development of cardiovascular maladaptation in rats. We found that sedentary rats treated with 5-FU presented with an increase in aortic pulse wave velocity—an established marker of aortic stiffness—over the course of the two-hour infusion. Importantly, this finding was not apparent in control groups treated with volume matched saline, or the exercise preconditioned 5-FU group, suggesting potential utility of exercise preconditioning in the prevention of 5-FU-induced vascular changes. Reverse phase protein analysis identified differential expression of several proteins involved in focal adhesion and/or cytoskeletal regulation pathways in aortic lysate from 5-FU treated rats, offering an exciting direction for future investigation into the mechanisms of 5-FU cardiotoxicity. Taken together, the findings presented in this dissertation provide new insight into the effects of 5-FU on the vasculature as well as offer a potential modality to alleviate some of the off-target cardiovascular side effects associated with 5-FU. It is our hope that our group and others can continue to build upon these findings to help ensure patients can continue to receive this efficacious treatment without increased risk to short and/or long-term cardiovascular wellbeing.
Keywords: 5-fluorouracil; Cardio-oncology; Cardiotoxicity; Chemotherapy; Cancer treatment; Vascular dysfunction